Bilateral congenital macular coloboma and cataract: A case report. Issue 11 (March 2019) - Zhang, Canwei; Wu, Peng; Wang, Luping; Gao, Jing; Huang, Xudong; Jiang, Yaqin
Abstract: Rationale: The case with congenital macular coloboma and cataract was rarely reported, and the pathogenic gene of the disease is still not clear. Moreover, it is difficult to improve the visual acuity of the eye with this disease. Patient concerns: An 11-year-old boy presented low visual acuity and horizontal nystagmus in both eyes. Ophthalmologic examination showed the patient with bilateral congenital coloboma and cataract. The visual acuity of the patient improved slightly after cataract surgery. Heterozygous mutations of frizzled-4 (FZD4) and nucleotide-binding oligomerization domain-containing protein 2 (NOD2) were identified by next-generation sequencing in this case. Diagnosis: Congenital macular coloboma and cataract of both eyes. Interventions: We performed the standard phacoemulsification and intraocular lens implantation on both eyes of the patient for the treatment of congenital cataract, and then followed up the fundus lesions regularly. Outcomes: Cataract surgery may improve the visual acuity of the eyes with congenital macular coloboma and cataract at some degree, but the vision of this patient was still very poor postoperatively. Furthermore, the heterozygous mutations of FZD4 and NOD2 were found in this patient. Lessons: Cataract surgery may improve the visual acuity of the eyes with congenital macular coloboma and cataract at some degree, and heterozygous mutations of FZD4 and NOD2 may be involved in the occurrence of congenital macular coloboma and cataract.